The Challenge of Mastering Arabic Language and Its Relation to the Ability to Read Kitab Kuning among Students in Tapal Kuda Islamic Boarding School - Suryadinata; Achmad Naufal Irsyadi; Zarkasi; Moh Hasyim Rosyidi; Yuana Dwi Agustina (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
Arabic language (AL) proficiency is a crucial element in understanding classical Islamic texts, or Kitab Kuning (KK), and plays a central role in the curriculum of pesantren (Islamic boarding schools). However, students often face difficulties mastering Arabic due to its complex grammar and vocabulary. This study aims to identify the challenges faced in mastering Arabic and the relationship between Arabic proficiency and the ability to read KK among students, particularly in Pesantren in Tapal Kuda region. This research employs a descriptive qualitative method. Data were collected from members of pesantren families in Tapal Kuda region, including Kyai, Nyai, Ning, Lora, pesantren administrators, as well as teachers (Ustadz and Ustadzah) and students. Data collection was carried out through observation and conversation methods with recording and note-taking techniques, as well as reflective introspective methods. Interviews were conducted to explore factors influencing Arabic proficiency and its impact on the ability to read KK. The collected data were analyzed through reduction, classification, verification, tabulation, and interpretation. The study's findings indicate that: 1) Arabic serves as an academic identity of pesantren; 2) Arabic is a central medium in KK; 3) Issues related to Arabic proficiency in the context of KK. Besides, the research findings include several factors and recommendations, namely; 1) factors impeding Arabic mastery include limited access to adequate educational resources, ineffective teaching methods, and variations in students' educational backgrounds; and 2) the findings suggest that the ability to read KK is significantly affected by the level of Arabic proficiency, particularly in aspects of grammar and vocabulary understanding. This study is expected to contribute to the development of more effective Arabic teaching strategies in pesantren and improve students' abilities to read and comprehend KK.